Conquering the Arctic and Conquering the Sky: Views on Technical Progress and Superman in Saint-Exupéry’s Night Flight and P. O. Sundman’s The Flight of the Eagle - Bourguignon, Annie (Nordlit, 2008)
Night Flight is a novel about a pilot, Fabien, getting caught in a storm at night while carrying mail from Patagonia to Buenos Aires. Losing his way, it becomes certain that he will perish, as the plane is running out of fuel. Per Olof Sundman’s The Flight of the Eagle is an historical novel about the Swedish engineer Andrée’s attempt to reach the North Pole in a balloon in 1897. The balloon trip starts from Danes Island, one of the Spitsbergen islands, and flies for about three days, but it has to be given up by the men on the expedition at a point far away from the Pole. They try to make their way on the ice-pack back to Spitsbergen but die at the beginning of the winter.